2011
DOI: 10.1176/appi.ajp.2011.11010087
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in the Antipsychotic Treatment of Psychiatric Outpatients With Anxiety Disorders

Abstract: Although little is known about their effectiveness for anxiety disorders, antipsychotic medications are becoming increasingly prescribed to psychiatric outpatients with these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
1
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 37 publications
6
64
1
3
Order By: Relevance
“…Nevertheless, increasing rates of antipsychotic treatment of young people 49 and common adverse metabolic effects 50 contribute to concerns over antipsychotic prescribing patterns to young people. 42,49,51 This study advances knowledge on the patterns of psychotropic medication use in a nationally representative sample of adolescents with well-characterized DSM-IV mental disorders and clinical correlates. Previous estimates of psychotropic medication use from pharmacy and insurance statistics are not based on representative samples of the population nor do they include comprehensive assessment of current mental disorders.…”
Section: Commentmentioning
confidence: 85%
“…Nevertheless, increasing rates of antipsychotic treatment of young people 49 and common adverse metabolic effects 50 contribute to concerns over antipsychotic prescribing patterns to young people. 42,49,51 This study advances knowledge on the patterns of psychotropic medication use in a nationally representative sample of adolescents with well-characterized DSM-IV mental disorders and clinical correlates. Previous estimates of psychotropic medication use from pharmacy and insurance statistics are not based on representative samples of the population nor do they include comprehensive assessment of current mental disorders.…”
Section: Commentmentioning
confidence: 85%
“…Due to the elevated and increasing worldwide prevalence of neuropsychiatric disorders (10% of adults, according to an 2006 estimation of the World Health Organization (Albrecht, 2006)) the use of antipsychotic drugs has expanded dramatically over the last decade (Alessi-Severini et al, 2012;Bulloch et al, 2012;Comer et al, 2011;Pascual et al, 2010). This increase was also potentiated by the introduction of "second generation" or atypical antipsychotics such as quetiapine, risperidone, olanzapine, clozapine and aripiprazole (Kessler et al, 2003), which in contrast to "first generation" or typical antipsychotics, have a higher clinical efficacy and a lower risk of inducing adverse extrapyramidal symptoms (movement disorders) (Monshat et al, 2010;Shah et al, 2011).…”
Section: Antipsychotic Drugsmentioning
confidence: 99%
“…There have been changes reported in the patterns of use of some medications over time and across countries because of the introduction of new products, controversies over which drugs are better and more effective, and each country imprinting its own particular culture. 6 In a US national study 7 the number of polypharmacy psychotropics prescribed has significantly increased from 1996 to 2007. Sanyal et al, 8 analyzing the national Canadian survey data, found that 49.3% of respondents with past-year major depression used ADs and benzodiazepines in 2002.…”
Section: Limitationsmentioning
confidence: 99%